LAGEYAN BAWOR DALAM CERITA “BAWOR DADI RATU” SEBAGAI PENDEKATAN PENDAMPINGAN BERBASIS BUDAYA DI ERA GLOBAL - Renoardi, Amos; Engel, Jacob Daan; Suwarto, Suwarto (Jurnal Ilmu Budaya, 2024)
This research aims to produce effective culture-based mentoring principles to preserve the value of local wisdom and ethical education in the Banyumasan Javanese community. This research was motivated by the fact that cultural values have been displaced in the modern era while recognizing the importance of exploring the local wisdom of Pakeliran Banyumasan as a value that needs to be explored and preserved. This research uses a qualitative method with an ethnographic approach. Observation, interviews, and documentation were used to collect data in this study, so that the principles of culture-based mentoring based on Bawor's lageyan in the story "Bawor Dadi Ratu" were obtained. The results showed that Bawor's lageyan includes cablaka, mbanyol, semblothongan, ksatria, and cancudan. The five lageyan contain noble values as special capital for the Banyumasan Javanese community to navigate life in the global era. Lageyan ksatria and cancudan are important parts of facing the dualism of modern times that separates humans from nature, so that individuals in society can maintain the value of mutual cooperation. Lageyan cablaka, mbanyol, and semblothongan have become an important part of dealing with the dualism of relationships due to technological developments. Lageyan Bawor emphasizes the principle of legitimacy or partnership that allows the values of mutual feelings, mutual acceptance, unity, harmony, brotherhood, and friendship to be maintained. Lageyan Bawor contains the principle of cultural mentoring as an effort to preserve values and ethical education in the context of relational mentoring.